Persons with Disabilities: Issues in Health Care Financing and Service Delivery - Clauser, Steven B.; Wiener, Joshua; Kennell, David L. (Rowman & Littlefield Publishers, 2010)
A key issue in the debate about reforming the U.S. health care system is how to finance and organize the delivery of long-term care. This volume offers perspectives on several important facets of this problem, including the regulation of private long-term care insurance, catastrophic out-of-pocket costs, and the use of long-term care and acute care services by the chronically disabled elderly. In addition to the editors, the contributors are Lisa Alecxih, David Kennell, and John Corea, Lewin-VHI; Brian Burwell and William Crown, SysteMetrics; Terry Coughlin, Korbin Liu, and Sharon Long, Urban Institute; Judith Kasper, Johns Hopkins University; Kenneth Manton and P.J. Eric Stallard, Duke University; Jennifer Schore, Mathematica Policy Research; Catherine Sullivan, Brookings; and Bruce Vladeck, Health Care Financing Administration. Dialogues on Public Policy